2021
DOI: 10.1155/2021/6698100
|View full text |Cite
|
Sign up to set email alerts
|

The Gingiva from the Tissue Surrounding the Bone to the Tissue Regenerating the Bone: A Systematic Review of the Osteogenic Capacity of Gingival Mesenchymal Stem Cells in Preclinical Studies

Abstract: The current review aims to systematically assess the osteogenic capacity of gingiva-derived mesenchymal stem cells (GMSCs) in preclinical studies. A comprehensive electronic search of PubMed, Embase, Web of Science, and Scopus databases, as well as a manual search of relevant references, was performed in June 2020 without date or language restrictions. Eligibility criteria were the following: studies that compared mesenchymal stem cells (MSCs) derived from the gingiva with other MSC sources (in vitro or in viv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 93 publications
(255 reference statements)
0
3
0
Order By: Relevance
“…GMSCs which not only show the potential for self-renewal and multi-differentiation but also have immunomodulatory, anti-inflammatory, and effective tissue regeneration properties can easily be obtained from gum tissues ( Liu et al, 2015 ; Al-Qadhi et al, 2021 ). MiR-21-5p overexpressed in TNF-α-stimulated GMSCs-Exo which reduces inflammation and death of mouse primary retinal ganglion cells and microglia simultaneously.…”
Section: Ascs-exo-lncrnas With Diverse Organ Sourcesmentioning
confidence: 99%
“…GMSCs which not only show the potential for self-renewal and multi-differentiation but also have immunomodulatory, anti-inflammatory, and effective tissue regeneration properties can easily be obtained from gum tissues ( Liu et al, 2015 ; Al-Qadhi et al, 2021 ). MiR-21-5p overexpressed in TNF-α-stimulated GMSCs-Exo which reduces inflammation and death of mouse primary retinal ganglion cells and microglia simultaneously.…”
Section: Ascs-exo-lncrnas With Diverse Organ Sourcesmentioning
confidence: 99%
“…68 GMSCs exhibited a moderate osteogenic capability, similar to PDLSCs; however, GMSCs were stronger at forming mineralized nodules and differentiated into osteogenic, chondrogenic, and adipogenic lineages. 69 While some studies suggest that inflamed GMSCs have a reduced capability for osteogenic and adipogenic differentiation than healthy subjects, epigenetic variables linked to chronic periodontitis could impact the cell line's different orientations. The “real mesenchymal stem cells”, the OPSCs have the characteristics to differentiate into osteoblasts and chondroblasts.…”
Section: Boundless Regenerative Potential Of Periodontal Stem Cellsmentioning
confidence: 99%
“…GMSCs lack tumorigenicity and can give rise to osteoblasts, chondroblasts, adipocytes, and keratinocytes (Santamaría et al, 2017;Murugan Girija et al, 2018). Several in vivo studies confirmed the ability of GMSCs in bone defects regeneration (Al-Qadhi et al, 2021). The osteogenic capability of GMSCs can be stimulated by proinflammatory cytokines and stress response proteins during inflammation (Tomasello et al, 2017).…”
Section: Gingival Mesenchymal Stem Cellsmentioning
confidence: 99%